Sharp function boundedness for vector-valued multilinear singular integral operators with non-smooth kernels - Liu Lanzhe (Հայաստանի ԳԱԱ)
Sharp function inequalities for several vector-valued, multilinear singular integral operators with non-smooth kernels are obtained. As an application, some weighted Lp(p > 1) norm inequalities for the vector-valued multilinear operators are derived.
Keywords: Mathematics; Science